Endothelial progenitor cells from aged subjects display decreased expression of sirtuin 1, angiogenic functions, and increased senescence. (15th June 2018) - Kaur, Impreet; Rawal, Preety; Rohilla, Sumati; Bhat, Mohsin H.; Sharma, Priyanka; Siddiqui, Hamda; Kaur, Savneet
Abstract: Studies have demonstrated that aging is associated with a substantial decline in numbers and angiogenic activity of endothelial progenitor cells (EPCs). In view of senescence being an important regulator of age‐related cell survival and function, in the current study, we correlated EPCs numbers and functions with their senescence status and mechanisms in young and elderly subjects. Healthy young subjects (n = 30, below 60 y) and old subjects (n = 30, equal to or above 60 y) participated in the study. Subjects had no significant disease or risk factors of disease and aging was the only risk factor in the aged subjects. Enumeration of CD34‐vegfr2 dual positive EPCs was performed. The ex vivo culture of EPCs was done to study colony formation, migration, and senescence‐associated beta‐galactosidase activity. The expression of cell cycle and senescence regulatory proteins including, p53, p21, and sirtuin 1 (SIRT1), a deacetylase protein was studied in cultured EPCs by RT‐PCR and immunofluorescence staining. In vivo proliferation, ex vivo colonies, migration, and secretory ability of EPCs was significantly higher in young subjects than that in elderly subjects. EPCs in old subjects showed enhanced senescence and decreased expression of SIRT1 in comparison to that observed in young subjects. An inhibition of SIRT1 in EPCs of young subjects led to significant increase in senescence and reduction of cell differentiation. The study suggests that EPCs have decreased proliferation and functions in aged subjects due to increased senescence which may be attributable to decreased expression of SIRT1.